Relationships between rain volume and the number of mushroom poisoning patients in Ubon Ratchathani Province - Nualanan, Pannipa; Jayathavaj, Vadhana (UBRU Journal for Public Health Research, 2024)
This research aimed to study the relationship and risk ratio in the form of incident rate ratio between monthly rainfall and the number of patients with mushroom poisoning in Ubon Ratchathani province. The Monthly rainfall data were collected from the National Hydroinformatics Data Center, Hydro - Informatics Institute (Public Organization), and the number of monthly mushroom poisoning cases were collected from the Disease Surveillance Reporting System 506, Bureau of Epidemiology, Department of Disease Control, as monthly data between January 2018 and July 2024. Statistical analysis was performed with Pearson’s correlation and the generalized linear model, processed with the jamovi statistical analysis program. The result showed that there was a moderate positive relationship between monthly rainfall (minimum, daily average, maximum) and the number of monthly mushroom poisoning cases (Pearson’s correlation coefficients greater than 0.531,0.534, and 0.542, p-value<.001, respectively). The negative binomial model with monthly average daily rainfall as the independent variable was the most consistent with the data, it had a coefficient of determination of 0.434, there was the coefficient of the model – the incident rate ratio ( ) that was statistically significant (p-value <.001) with an average (intercept) of 44.27 cases and the coefficient of monthly average daily rainfall was 1.01. That is, if the monthly average daily rainfall increases by 1 mm, there will be an increase of 1 percent of patients from the monthly average number of patients. The number of mushroom poisoning cases in Ubon Ratchathani province did not have a linear relationship with the monthly average daily rainfall. When the monthly average daily rainfall increases by 1 mm, the number of cases increases by 1 percent from the average monthly number of mushroom poisoning cases.